Photodetectors for HESS - Kohnle, Anton; Mattes, J.; Hermann, G.; Hofmann, Werner; Panter, Michael (Nuclear instruments & methods in physics research. Section A, Accelerators, spectrometers, detectors and associated equipment, 2000)
HESS is a next-generation array of imaging atmospheric Cherenkov telescopes (IACTs) for the detection of cosmic gamma rays above 40 GeV, to be built in the Southern Hemisphere in the Khomas Highland of Namibia. In its final stage, the HESS experiment will consist of up to 16 telescopes each with a 80 m2 reflector and 15 m focal length. The schedule foresees to start with scientific operation of the first 4-telescope subsystem in 2002 (Phase 1). In the focal plane, each of the cameras contains ∼700 photomultiplier pixels each viewing 0.16° of the sky, giving a total field of view of 4.3°. A large part of the trigger electronics, analog signal storage, and control and monitoring electronics are integrated in the camera.
Gesehen am 18.11.2020